1999
DOI: 10.1093/tropej/45.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Intestinal parasites in Malaysian children with cancer

Abstract: In this prospective study, we examined stool specimens from children with cancer receiving chemotherapy who were admitted for fever to the Universiti Sains Malaysia Hospital in Kota Baru, Kelantan. Stool specimens were examined for ova and cysts of parasites. Over a period of 15 months, there were 129 febrile episodes in 50 children with cancer and, in all, 237 stool specimens were examined. Sixty-six per cent of febrile episodes were associated with neutropenia and 9 per cent were associated with diarrhoea. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
3
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 0 publications
4
28
3
2
Order By: Relevance
“…In this study, the rate of intestinal parasitic infection in immunocompromised children with persistent and/or recurrent diarrhoea was 57%, slightly higher than that found in a similar study in Malaysia (42%) [7] on paediatric cancer patients and one on HIV-positive children in Thailand (33%) [13]. The difference could be due to different epidemiological patterns of parasitic infection in Indonesia.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In this study, the rate of intestinal parasitic infection in immunocompromised children with persistent and/or recurrent diarrhoea was 57%, slightly higher than that found in a similar study in Malaysia (42%) [7] on paediatric cancer patients and one on HIV-positive children in Thailand (33%) [13]. The difference could be due to different epidemiological patterns of parasitic infection in Indonesia.…”
Section: Discussioncontrasting
confidence: 50%
“…The incidence of parasitic infection in HIV patients with diarrhoea was reported to be 53-83% [5,6]. Similar prevalence rates (42%) were also found in children with malignancy [7].…”
Section: Introductionmentioning
confidence: 63%
“…By comparison, 13% of stools from non-oncology patients were positive. The second study was performed in Malaysia, where Cryptosporidium was found in 2% of children (86).…”
Section: Cryptosporidiosis In Patients With Malignant Diseasementioning
confidence: 99%
“…Subsequently, studies on cryptosporidiosis have been limited to hospital cases. The incidence of cryptosporidiosis among paediatric patients ranged from 1-11% (Mendez et al 1988;Mat Ludin et al 1991;Lai 1992;Kan & Shekhar 1993;Ng & Shekhar 1993;Menon et al 2001) and among immunosuppressed children, suffering from cancer and receiving chemotherapy, was 2% (Menon et al 1999). In a community study of diarrhoeic young children in Kelantan, 11% had cryptosporidiosis (Lai 1992).…”
Section: Cryptosporidiummentioning
confidence: 99%
“…Among hospitalized children, a high incidence (25%) of giardiasis was observed in Orang Asli children (Bisseru & Aziz 1970). In children with cancer and undergoing chemotherapy, giardiasis was observed in 6% of the patients (Menon et al 1999).…”
Section: Giardiamentioning
confidence: 99%